Involvement Modulates the Effects of Deception on Memory in Daily Life - Li, Yan; Liu, Zhiwei (Frontiers in Psychology, 2021)
Previous studies have demonstrated that liars who adopt a false denial strategy often forget what they lied about, which has been labeled the denial-induced forgetting (DIF) effect. However, several investigations have not found such an effect. It has been suggested that involvement might play a role in the inconsistency. The present study was designed to directly determine whether involvement modulates the effects of deception on memory. Participants were assigned randomly to either high- or low-involvement conditions and were required to complete a mock shopping task. They were then asked to participate in an interview in which they were asked to respond honestly or deceptively. Two days later, final memory tests were given, and the participants were asked to give honest responses. We found a DIF effect in the high-involvement condition but not in the low-involvement condition. Moreover, the liars in the high-involvement condition created more nonbelieved memories in the source memory test and the destination memory test than the honest participants. In addition, liars in both the high- and low-involvement conditions forgot who they lied to. We conclude that the effects of deception on memory could be influenced by the degree of involvement.